TRANSITION EFFECTS IN AGRAR IN SOME COUNTRIES OF CENTRAL AND SOUTH-EAST EUROPE - Nikolić, Marija; Katić, Branko (Economics of Agriculture, 2006)
By the end of twentieth century process of transition occurred in countries of formal planned economy and socialistic model of governance. In the analyses of achieved level of progress, three levels can be underlined: - Countries of central Eastern Europe witch accessed European Union in the last wave of accession in 2004. and in witch processes of transition are practically finished, - Countries that are now on doorstep of EU (Romania and Bulgaria), and - Serbia, where transition process are in delay of one decade, from known reasons: country decomposition, war in environment, isolation from international community, NATO actions. This paper works gives overview of applied measures and achieved effects of transition in the area of agrar in listed countries. With significant problems, it is showed that transition in countries that ended this process was successful. Serbia has, in a matter of speaking, stirring times by the end of transition. Experience obtained by countries that finished this process can be still useful for transition in Serbia.